CULTIVATING BRAND LOYALTY IN THE DIGITAL MARKETPLACE: EXPLORING THE INTERPLAY OF ONLINE ENGAGEMENT AND FEMININE IDENTITY AMONG COSMETIC CONSUMERS - Ni Putu Dewi Indrayati (Jurnal Manajemen Pendidikan, 2026)
This research explores the relationship between online engagement and feminine identity in developing brand loyalty among cosmetic consumers in the digital marketplace. The growth of social media has changed how cosmetic brands communicate with consumers, particularly women who express their self-image, confidence, and lifestyle through beauty products. The study aims to analyze the influence of digital interaction, emotional attachment, and feminine identity on consumer loyalty toward cosmetic brands. A qualitative descriptive approach was applied by involving cosmetic consumers who actively use digital platforms such as Instagram, TikTok, and online shopping applications. Data were gathered through interviews, online observations, and consumer responses related to cosmetic brand activities. The findings show that interactive digital content, influencer marketing, personalized communication, and emotional engagement contribute significantly to strengthening brand loyalty. In addition, feminine identity plays an important role in shaping purchasing decisions and long-term commitment to cosmetic brands. Consumers are more loyal to brands that reflect their personal values, beauty standards, confidence, and social identity. Therefore, effective cosmetic branding requires authentic digital engagement to maintain sustainable consumer loyalty.